Exploiting the therapeutic vulnerability of IDH-mutant gliomas with zotiraciclib - Ying Pang; Qi Li; Zach Sergi; Guangyang Yu; Olga Kim; Peng Lu; Marina Chan; Xueyu Sang; Herui Wang; Alice Ranjan; Robert W. Robey; Ferri Soheilian; et al. (iScience)
Summary: Isocitrate dehydrogenase (IDH)-mutant gliomas have distinctive metabolic and biological traits that potentially render them susceptible to targeted treatments. Here, by conducting a high-throughput drug screen, we pinpointed a specific vulnerability of IDH-mutant gliomas to zotiraciclib (ZTR). ZTR exhibited selective growth inhibition across multiple IDH-mutant glioma in vitro and in vivo models. Mechanistically, ZTR at low doses suppressed CDK9 and RNA Pol II phosphorylation in IDH-mutant cells, disrupting mitochondrial function and NAD+ production, resulting in oxidative stress. Integrated biochemical profiling of ZTR kinase targets and transcriptomics unveiled that ZTR-induced bioenergetic failure was linked to the suppression of PIM kinase activity. We posit that the combination of mitochondrial dysfunction and an inability to adapt to oxidative stress resulted in significant cell death upon ZTR treatment, ultimately increasing the therapeutic vulnerability of IDH-mutant gliomas. These findings prompted a clinical trial evaluating ZTR in IDH-mutant gliomas (NCT05588141).